Electronics all-in-one for dummies - Lowe, Doug, 1959- author (Hoboken, New Jersey : John Wiley & Sons, Inc., 2017)
If you're ready to take you basic electronics skills to the next level, this book provides exactly what you need! Lowe provides clear explanation of the important concepts, and includes building projects that will get you going from concept to conception
Getting started in electronics -- Working with basic electronic components -- Working with integrated circuits -- Beyond direct current -- Doing digital electronics -- Working with Arduino microprocessors -- Working with BASIC stamp processors -- Working with Raspberry Pi -- Special effects
Includes index.
Keywords: Electronics; Electronics -- Handbooks, manuals, etc